1987
DOI: 10.1161/01.cir.76.2.450
|View full text |Cite
|
Sign up to set email alerts
|

Balloon-expandable intracoronary stents in the adult dog.

Abstract: We studied the acute and chronic biological reaction to balloon-expandable intracoronary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
93
1
7

Year Published

1996
1996
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 339 publications
(106 citation statements)
references
References 18 publications
5
93
1
7
Order By: Relevance
“…9 There is a gradual thinning of the in-stent neointima in canine coronary arteries by 12 months after stenting, accompanied by reduced cellularity and increased fibrosis. 38 In a study of stented porcine coronary arteries, Kim et al 34 reported a 33% reduction in stent area stenosis at 6 compared with 2 months.…”
Section: Neointimal Regressionmentioning
confidence: 99%
“…9 There is a gradual thinning of the in-stent neointima in canine coronary arteries by 12 months after stenting, accompanied by reduced cellularity and increased fibrosis. 38 In a study of stented porcine coronary arteries, Kim et al 34 reported a 33% reduction in stent area stenosis at 6 compared with 2 months.…”
Section: Neointimal Regressionmentioning
confidence: 99%
“…These first stents were bare metal stents (BMS) and unfortunately were associated with a high incidence of subacute thrombosis in humans. [249,250]. This stent was subsequently modified to the Palmaz-Schatz stent, a heparin-coated stent [251][252][253].…”
Section: Intra-arterial Stentsmentioning
confidence: 99%
“…Metallic stents were invented to compensate the recoiling of stretched vessel. 2) Stents sufficiently reduced a risk of acute closure after PCI, however, there remained a problem named in-stent restenosis characterized by an excessive neointimal hyperplasia inside the stent, which became the major limitation of coronary stents. In early 2000s, the advent of drug eluting stents (DES) brought a hope to overcome the limitation of stents with its pharmacological suppression of neointimal hyperplasia, and succeeded to improve the restenosis rate after implantation.…”
Section: Introductionmentioning
confidence: 99%